Everyday discrimination and satisfaction with nature experiences - Schinasi, Leah H.; Lawrence, Jourdyn A. (Frontiers in Epidemiology, 2024)
There is growing interest in creating public green spaces to promote health. Yet, discussions about these efforts often overlook how experiences of chronic discrimination -which may manifest as racism, sexism, or homophobia, and more -could undermine satisfaction with nature experiences. Using data from the 2018 wave of the National Opinion Research Center (NORC) General Social Survey (GSS), we quantified associations of frequency of everyday discrimination, operationalized using the Everyday Discrimination Scale (EDS, the primary independent variable), with respondents' perceptions of nature experiences and with their reported time spent in nature. Specifically, we quantified associations with the following three variables: (1) dissatisfaction with day-to-day experiences of nature, (2) not spending as much time as they would like in natural environments, and (3) usually spending at least one day per week in nature. We used survey weighted robust Poisson models to estimate overall associations, and also stratified analyses by racial/ethnic and gender identity categories. Of 768 GSS respondents, 14% reported dissatisfaction with nature experiences, 36% reported not spending as much time as they would like in nature, and 33% reported that they did not spend at least one day per week in nature. The median non-standardized EDS, coded such that a higher value indicates greater frequency of discrimination, was 11 (interquartile range: 8, 15).Prevalence of reporting dissatisfaction with day-to-day experiences in nature was 7% higher in association with every one unit increase in EDS score above the median (PR: 1.07, 95% CI: 1.02 -1.11). The prevalence of reporting not spending as much time as one would like in nature was 2% higher for every unit increase in higher than median everyday discrimination frequency (PR: 1.02, 95% CI: 1.00 -1.05). Higher than median frequency in everyday discrimination was not associated with spending less than one day per week in nature. Race/ethnicity and gender identity did not modify associations. Greater frequency of everyday discrimination is associated with less satisfaction with experiences in nature. This relationship could undermine efforts to promote health equity through green interventions.